Giant Magneto-impedance Effect in Composite Wires with Different Core Layer - Wang, R. L.; Li, X.; Kong, X. H.; Guo, Y. X.; Ruan, J. Z.; Zhao, Z. J. (Nano-Micro Letters, 2013)
Composite structure materials were potential sensing elements for magnetic sensors due to Giant magnetoimpedance (GMI) effect. Two kinds of composite wires with different magnetic/non-magnetic structures were fabricated by using electroless deposition methods and the magnetoimpedance properties were investigated. The maximum GMI ratio of 114% was acquired at 60 MHz in the composite wires with a ferromagnetic core, whereas, 116% of maximum GMI ratio was found in the composite wires with a conductive core at low frequency of 600 kHz. These results exhibit that the GMI ratio reaches the maximum when magnetoresistance ratio ΔR/R and magnetoinductance ratio ΔX/X make the comparative contributions to the total magnetoimpedance (MI). The obvious GMI effect obtained in the composite wires with conductive core frequency may provide a candidate for applications in magnetic sensors, especially at low frequencies.